PERBANDINGAN MATERI MUATAN KETETAPAN MPR PADA MASA PEMERINTAHAN ORDE LAMA, ORDE BARU, DAN ERA REFORMASI - Widayati Widayati (UNISSULA, 2016)
Decree of People’s Consultative Assembly (TAP MPR) established since 1960 and 2002. Totally there are 139 Decrees in Consultative Assembly (TAP MPRS and TAP MPR). The whole Decree of People’s Consultative Assembly (TAP MPRS and TAP MPR) was formed during the reign of the Old Orde, the New Orde, and the Reformation Era. TAP MPR was changed in content material along with the change of government and the amendments of 1945 Constitution of The State of The Republic of Indonesia (UUD 1945). Therefore, this study will compare to the substance of the Decree of People’s Consultative Assembly (TAP MPR) on the government period. The method used in this research was normative juridical with secondary data, which was analyzed by the method of normative, then presented descriptively. The change of government affects the substance of the Decree of People’s Consultative Assembly (TAP MPR).